1998
DOI: 10.1074/jbc.273.19.11491
|View full text |Cite
|
Sign up to set email alerts
|

Pre-steady State of Reaction of Nucleoside Diphosphate Kinase with Anti-HIV Nucleotides

Abstract: The pre-steady-state reaction of Dictyostelium nucleoside diphosphate (NDP) kinase with dideoxynucleotide triphosphates (ddNTP) and AZT triphosphate was studied by quenching of protein fluorescence after manual mixing or by stopped flow. The fluorescence signal, which is correlated with the phosphorylation state of the catalytic histidine in the enzyme active site, decreases upon ddNTP addition according to a monoexponential time course. The pseudo-first order rate constant was determined for different concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 21 publications
6
62
0
Order By: Relevance
“…The inhibitory effect of CDP is 50-fold lower than that of GDP, demonstrating a base specificity of the inhibition. It is interesting to note that a similar base specificity has also recently been reported for the enzymatic activity of the human NDPK-B (45) and of the Dictyostelium enzyme (46). Moreover, analysis of the inhibition curve in the presence of GTP gives a K I equal to 40 M similar to that of GDP, confirming that formation of the phosphohistidine intermediate does not affect the binding of the oligonucleotide.…”
Section: Fig 1 Sedimentation Equilibrium Analysis Of Ndpk-bsupporting
confidence: 51%
See 1 more Smart Citation
“…The inhibitory effect of CDP is 50-fold lower than that of GDP, demonstrating a base specificity of the inhibition. It is interesting to note that a similar base specificity has also recently been reported for the enzymatic activity of the human NDPK-B (45) and of the Dictyostelium enzyme (46). Moreover, analysis of the inhibition curve in the presence of GTP gives a K I equal to 40 M similar to that of GDP, confirming that formation of the phosphohistidine intermediate does not affect the binding of the oligonucleotide.…”
Section: Fig 1 Sedimentation Equilibrium Analysis Of Ndpk-bsupporting
confidence: 51%
“…In the filterbinding assay, the oligonucleotide concentration used was near the dissociation constant, conditions in which the stoichiometry could be in error (47). In contrast, a fixed protein concentration and variable oligonucleotide concentrations, such that der et al (46) reported recently that the nucleotide analogue PAPS can adopt a new conformation inside the active site of Dictyostelium NDP kinase. Indeed, the 5Ј-phosphate of bound PAPS points out from the binding pocket, whereas the 3Ј-phosphate binds near the active site histidine.…”
Section: Discussionmentioning
confidence: 99%
“…This result was anticipated based on the previous study (38) and based on our biochemical data showing that increased dNTPs reduce AZT-TP and ddCTP inhibition of RT by active site competition. The reduction in drug efficacy observed in the cell culture experiments may also be influenced by competition for the active site of cellular kinases because NRTIs are not as efficiently phosphorylated as deoxyribonucleosides (33). Additionally, when VLPs ϩVpx were added to activated T cells, NRTI efficacy was decreased to a much lesser extent than VLP ϩVpx-treated macrophages (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the kinases expressed in macrophages are active enough to phosphorylate a high concentration of deoxyribonucleosides into dNTPs. However, nucleoside diphosphate kinase is not as active toward NRTIs as canonical dNTPs (33). Therefore, when the concentration of dNTPs increases, the dNTPs may out-compete NRTIs for the active site of nucleoside diphosphate kinase, resulting in a decreased concentration of NRTI-TPs.…”
Section: Effect Of Samhd1 On Hiv-1 Sensitivity To Nrtis In Thp-1mentioning
confidence: 96%
“…The enzyme is independent of the nature of the base and thus displays little specificity with respect to the nucleoside diphosphate and the natural triphosphate donor, although discrimination with respect to 2′,3′-dideoxynucleoside triphosphate donors has been reported (Bourdais et al, 1996;Deville-Bonne et al, 1996;Schneider et al, 1998). The enantioselectivity of the enzyme has not been studied except in the case of beef liver nucleoside diphosphate kinase, which phosphorylates both enantiomers of carbovir with a preference for the natural enantiomer .…”
Section: Nucleotide Kinasesmentioning
confidence: 99%